Encyclopedic Work on Nikolai Gogol - Vladimir A. Voropaev (Два века русской классики)
The article is a review of the monograph by I. A. Vinogradov “Gogol Encyclopedia. Works, Sketches, Preparatory Materials: in 7 vols., vol. 1: A–Zh.” A distinctive feature of the book is its comprehensive coverage. The encyclopedia, conceived in 7 volumes, promises to become an exhaustive information base, an important substantive and methodological reference point for scientists, students, teachers, and all admirers of Gogol. The work aims to summarize the one-and-a- half century of experience in Gogol scholarship and provide the reader with the opportunity to gain information about the most significant scientific discoveries in the study of his legacy. The review analyzes the detailed content of the work of a Gogol scholar known for his numerous works, the compiler of a systematic collection of documentary evidence about Gogol in 3 volumes, the author of a seven-volume chronicle of the writer’s life and work and several monographs.